Kinematic and dynamic analysis of compliant mechanisms considering both lateral and axial deformations of flexural beams. (February 2019) - Yu, Yue-Qing; Zhou, Peng; Xu, Qi-Ping
The kinematic and dynamic analysis of compliant mechanisms is investigated comprehensively in this work. Based on the pseudo-rigid-body model, a new PR model is proposed to simulate both the lateral and axial deformations of flexural beams in compliant mechanisms. An optimization for the characteristic factors and a linear regression for the stiffness coefficients of PR pseudo-rigid-body model are presented. Compared with the 1R and 2R pseudo-rigid-body model, the advantage of the PR model is well illustrated. The dynamic modeling of flexible beams in compliant mechanisms is then developed based on the PR pseudo-rigid-body model. The dynamic equation of a PR pseudo-rigid-body dynamic model is derived and the dynamic responses are then presented. The kinematic and dynamic analysis of a compliant slider-crank mechanism is presented by the 1R, 2R and PR model, respectively. The effectiveness of pseudo-rigid-body models and the superiorities of the PR pseudo-rigid-body model and PR pseudo-rigid-body dynamic model are shown clearly in the numerical example.